مكانة عمل أهل المدينة عند الإمام مالك بن أنس: The Position of the Practice of Ahlu al-Madīnah in the Perspective of al-Imām Mālik bin Anas - Rachmat bin Badani Tempo; Saifullah bin Anshor; Wahyuni Ishak (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The research in front of dear readers is about the practice of the people of Medina. Among the objectives were: To identify the essence of the practice of people of Medina and its position according to Imam Malik and other scholars. The researchers focuses on two points, the first: the essence of the people of Medina, and the second: What is the position of the people of Medina according to Imam Malik bin Anas and other scholars? The type of research employed was library research that focuses on texts from books and interesting results of scientific research related to the topic. The results show: First, the practice of the people of Medina is propositions or arguments which are disputed, this is due to differences in understanding the concept. Second, the practice of the people of Medina is divided into two parts, one of which is through excerpts which consist of four types: excerpts of the speech, acts, consent and neglect, and this is an agreed statement. The second one is based on ijtihad, Imam Malik's companions differ in this respect. Third, the practice of people of Medina according to Imam Malik has a great position because of the prominence of the city of Medina and its people compared to other regions based on several narrations mentioned by the Prophet sallallaahu 'alaihi wasallam and his companions, may Allah be pleased with them all. Imam Malik had deduced the law from several problems based on the practice of people of Medina, had often referred to it in different terms in his Muwatta, and had given priority to the practice of the people in Madina if it is contradicting to khabar wahid. He has written letters against people who disagree with him regarding the practice of people of Medina in his time including his famous treatise to Al-Laits bin Saad. Fourth, in contrast to Imam Malik, the majority of scholars do not consider the practice of the people of Medina as a proposition because they see that perfection belongs to the ummah as a whole, and the people of Medina are not the whole ummat, even outside the city of Medina some scholars are more knowledgeable than the people of Medina.